Pelaksanaan Pendidikan Agama Buddha Pada Sekolah Dasar - Winja Kumari; Lisniasari Lisniasari (Universitas Persada Indonesia YAI, 2021)
The research was conducted with a descriptive qualitative approach. The purpose of thisstudy was to determine the implementation of Buddhist education in elementary schools. In thisstudy, a method known as descriptive qualitative method was used. The research method isdescriptive qualitative by describing an event, current event. In other words, this method takes aproblem from an actual problem. The learning process of Buddhist teaching subjects, forBuddhist students, at the elementary school level, can be described by applying teachingmaterials/materials, applying tactics/systems, applying media and applying assessments. Theconclusions of this study are the implementation of Buddhist education at the elementary schoollevel still reaping many problems ranging from the competence of Buddhist education teacherswho are still lacking, the media used is still limited, training programs are still lacking, andvarious facilities and infrastructure are not adequate. So that various evaluations are needed sothat the implementation of Buddhist education at the elementary school level can run well